Adhoc Apparatus Quality Improvement Model: Recruitment And Selection System - Zulkifli Sultan; Abdul Rahman Rahim; Dian Fitri; Roman Klimko (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
The quality of human resources has an important role in the organization's sustainability, so the recruitment and selection process is carried out according to existing procedures, especially supported by technology-based systems. This research aims to analyze the relationship between recruitment and selection in producing quality human resources using a model utilizing an online-based system. Researchers used a mixed method approach to complete what had been formulated, reaching 114 samples employing simple random sampling. Data was obtained by distributing questionnaires and conducting interviews using the FGD method with the implementing committee and selected District Panwaslu members. Data from the questionnaire research were analyzed utilizing structural equation modeling (SEM), while data from interviews were analyzed using data triangulation. The results found that information and communication technology systems significantly influenced recruitment, selection, and quality of human resources. Meanwhile, the recruitment and selection process did not significantly influence the production quality of human resources since optimal recruitment and selection did not guarantee that the selected human resources were of good quality. However, the role of selection could mediate the relationship between technological systems in creating quality human resources, while recruitment cannot.